Rewriting of the Past: Postmodern Intertextuality in The Peak by Sarubhakta - Pun, Min (SCHOLARS: Journal of Arts & Humanities, 2019)
According to Linda Hutcheon, postmodern intertextuality desires to close the gap between past and present of the reader and desires to rewrite the past in a new context. The use of postmodern intertextuality in Sarubhakta’s The Peak [an English translation from his original Nepali version short novel Chulee] has some relation with a fictional work from the past. There are some visible links between Sarubhakta’s novel and Hemingway’s short novel The Old Man and the Sea as both novels revolve around the theme of adventure. The major objective of this paper, therefore, is to indentify Sarubhakta’s book as an adventure novel, having some intertextual connections with Hemingway’s book. As a number of books in this category are surprisingly large, in this paper, only Sarubhakta’s book has been studied making comparisons to Hemingway’s book. Sarubhakta’s novel is the text that adheres to postmodern intertextuality as it challenges the concept of originality and the question of whether rewriting another author’s text is not a good piece of writing.